Peningkatan Level Berpikir Aljabar Siswa Berdasarkan Taksonomi SOLO Pada Materi Persamaan Linier Melalui Pemberian Scaffolding - Anis Farida Jamil (Lembaga Penelitian dan Pendidikan Mandala, 2017)
The aim of this research is to describe students’ level of algebraic thinking based on SOLO model in linier equation material and improving students’ level of algebraic thinking by giving scaffolding to students. This research was done to the eighth grade students of Muhammadiyah 1 Malang Junior High School who have already learnt about linier equation. Six students were taken as the subjects of the research with the specification that two students had unistructural level of algebraic thinking, other two students had multistructural level of algebraic thinking, and the last two students had relational level of algebraic thinking. Based on the result of the research, the researcher finds that students’ levels of algebraic thinking were increased by giving scaffolding in written test 1. One of two students with unistructural level of algebraic thinking could increase the level into multistructural and the other could increase the level into relational. Other two students who were in multistructural level of algebraic thinking, both of them, could increase the level into extended abstract level. In addition, the last two students with relational level of algebraic thinking, both of them, could increase their level into extended abstract level.